Managing correctional treatment for reduced recidivism: a meta-analytic review of programme integrity - Andrews, Donald A. (Legal and criminological psychology, 2005)
Purpose. Although issues surrounding programme integrity and implementation seem intuitively appealing as important contributors to effective correctional programming, they have been relatively ignored within the extant literature. The present meta-analysis provided the first systematic examination of these issues by exploring their impact on recidivism reduction in correctional treatment programmes. Methods. A meta-analysis was conducted on 273 tests of the effectiveness of correctional treatment programmes that were extracted from various human service programmes. Indicators of programme integrity reviewed included several management variables (i.e. selection, training and clinical supervision of service deliverers), evaluator involvement, presence of training manuals, monitoring of treatment delivery, and using a small sample of clients. Results. Overall, the meta-analyses revealed that programme integrity provided an independent source of enhanced programme effectiveness, even when controls were introduced for other variables (e.g. involved evaluator and sample size). Conclusions. Consistent with previous research, the present study demonstrated that the positive contributions of programme integrity were limited to the enhancement of the effects of human service programmes consistent with the principles of risk, need, and general responsivity. However, the relatively poor reporting of programme integrity indicators within primary studies necessitates that evaluators and programme deliverers alike ensure that this information is included in future evaluations to provide an even greater understanding of the influences of integrity.